Clinical Characteristics and Outcomes of Pediatric Cerebral Venous Sinus Thrombosis: An Analysis of 30 Cases in China - Wang, Xin-Hua; Zhang, Lin-Mei; Chai, Yi-Ming; Wang, Ji; Yu, Li-Fei; Zhou, Shui-Zhen (Frontiers in Pediatrics, 2019)
Background: Cerebral venous sinus thrombosis (CVST) in children is rare in a clinical setting. The aim of this study was to summarize the etiological, clinical, and imaging characteristics of CVST in children. Methods: We retrospectively analyzed the data of 30 patients with a diagnosis of CVST who were admitted to Children's Hospital of Fudan University from 2008 to 2018. The medical records, including clinical manifestations, laboratory data, neurological findings, treatment, and short-term prognosis were analyzed. Results: Etiologically, the causes of CVST were infection (7/30), tumor (3/30), nephritis or nephrotic syndrome (8/30), traumatic brain injury (1/30), and undefined disease (11/30). All 30 cases were diagnosed with CVST after a neuroimaging examination using brain magnetic resonance imaging (MRI) combined with magnetic angiography venography (MRV). With regard to short-term prognosis, all the patients were treated with anticoagulants, after which 26 cases improved. Conclusions: CVST patients do not typically present with specific clinical manifestations, which leads to a high rate of misdiagnosis and delayed therapy. Increased consideration and prompt MRV checkup plays a key role in achieving an accurate diagnosis. Overall, anticoagulation is a safe and effective treatment for CVST.